Unravelling the regulation pathway of photosynthetic AB‐GAPDH. Issue 11 (27th October 2022) - Marotta, Roberto; Del Giudice, Alessandra; Gurrieri, Libero; Fanti, Silvia; Swuec, Paolo; Galantini, Luciano; Falini, Giuseppe; Trost, Paolo; Fermani, Simona; Sparla, Francesca
Abstract : Regulation of the heteromeric form of photosynthetic glyceraldehyde 3‐phosphate dehydrogenase (AB‐GAPDH) depends on oscillation between a fully active heterotetramer (A2 B2 ) and inhibited oligomers. Experimental evidence demonstrates that the inhibition of spinach AB‐GAPDH depends on the formation of dimers, tetramers or pentamers of A2 B2 modules linked together by C‐terminal extensions of the B subunits that extend from one modular tetramer and occupy two active sites of the adjacent tetramer. Abstract : Oxygenic phototrophs perform carbon fixation through the Calvin–Benson cycle. Different mechanisms adjust the cycle and the light‐harvesting reactions to rapid environmental changes. Photosynthetic glyceraldehyde 3‐phosphate dehydrogenase (GAPDH) is a key enzyme in the cycle. In land plants, different photosynthetic GAPDHs exist: the most abundant isoform is formed by A2 B2 heterotetramers and the least abundant by A4 homotetramers. Regardless of the subunit composition, GAPDH is the major consumer of photosynthetic NADPH and its activity is strictly regulated. While A4 ‐GAPDH is regulated by CP12, AB‐GAPDH is autonomously regulated through the C‐terminal extension (CTE) of its B subunits. Reversible inhibition of AB‐GAPDH occurs via the oxidation of a cysteine pair located in the CTE and the substitution of NADP(H) with NAD(H) in the cofactor‐binding site. These combined conditions lead to a change in the oligomerization state and enzyme inhibition. SEC–SAXS and single‐particle cryo‐EM analysis were applied to reveal the structural basis of this regulatory mechanism. Both approaches revealed that spinach (A2 B2 ) n ‐GAPDH oligomers with n = 1, 2, 4 and 5 co‐exist in a dynamic system. B subunits mediate the contacts between adjacent tetramers in A4 B4 and A8 B8 oligomers. The CTE of each B subunit penetrates into the active site of a B subunit of the adjacent tetramer, which in turn moves its CTE in the opposite direction, effectively preventing the binding of the substrate 1, 3‐bisphosphoglycerate in the B subunits. The whole mechanism is made possible, and eventually controlled, by pyridine nucleotides. In fact, NAD(H), by removing NADP(H) from A subunits, allows the entrance of the CTE into the active site of the B subunit, hence stabilizing inhibited oligomers.